THE HISTORY OF SURGICAL TREATMENT OF GASTROESOPHAGEAL REFLUX DISEASE - I. S. Tarbaev; A. M. Akhmatov; D. I. Vasilevskii; G. M. Rutenburg (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The most important historical stages of formation of scientific ideas of gastroesophageal reflux and its complications are presented in the article; the main milestones in the development of gastroesophageal reflux disease surgery are reflected.